Political Competition and State Capacity Evidence from a Land Allocation Program in Mexico (2020)
We develop a model of the politics of state capacity building undertaken by incumbent parties that have a comparative advantage in clientelism rather than in public goods provision. The model predicts that, when challenged by opponents, clientelistic incumbents have the incentive to prevent investments in state capacity. We provide empirical support for the model¿s implications by studying policy decisions by the Institutional Revolutionary Party (PRI) that affected local state capacity across Mexican municipalities and over time. Our difference-in-differences and instrumental variable identification strategies exploit a national shock that threatened the Mexican government¿s hegemony in the early 1960s. The intensity of this shock, which varied across municipalities, was partly explained by severe droughts that occurred during the 1950s.